2010
DOI: 10.1021/jp106850f
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Thiophene Dendrimer with an Electron-Withdrawing Core and Electron-Rich Dendrons: How the Molecular Structure Affects the Morphology and Performance of Dendrimer:Fullerene Photovoltaic Devices

Abstract: The combination of electron-rich and electron-poor moieties in conjugated molecules is frequently utilized in order to red shift the absorption spectrum and improve photon harvesting in bulk heterojunction photovoltaic devices. In this study we characterize a conjugated thiophene dendrimer that has an electron-withdrawing core and electron-rich dendrons in order to investigate the effects of this design approach on the salient properties that influence the performance of photovoltaic devices with this dendrime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
(103 reference statements)
1
27
0
1
Order By: Relevance
“…For this reason, we expect changes in the microstructure of the polymer to have little influence on the mobility measured via TRMC. An example of this insensitivity to long‐range order can be found in our previous work on dendrimers having oligothiophene branches: the relatively disordered dendrimers exhibited TRMC hole mobilities identical to neat regioregular P3HT films of a higher degree of crystallinity 57. Similarly, Dicker et al previously observed, in combined pulse‐radiolysis and flash‐photolysis TRMC experiments, that there was no discernable difference in the GHz hole mobility between regioregular and regiorandom P3HT, which had field‐effect transistor hole mobilities differing by up to two orders of magnitude 58.…”
Section: Resultsmentioning
confidence: 80%
“…For this reason, we expect changes in the microstructure of the polymer to have little influence on the mobility measured via TRMC. An example of this insensitivity to long‐range order can be found in our previous work on dendrimers having oligothiophene branches: the relatively disordered dendrimers exhibited TRMC hole mobilities identical to neat regioregular P3HT films of a higher degree of crystallinity 57. Similarly, Dicker et al previously observed, in combined pulse‐radiolysis and flash‐photolysis TRMC experiments, that there was no discernable difference in the GHz hole mobility between regioregular and regiorandom P3HT, which had field‐effect transistor hole mobilities differing by up to two orders of magnitude 58.…”
Section: Resultsmentioning
confidence: 80%
“…prepared star‐shaped molecules 155 and 156 to show, how a systematic modification of the core unit can change the properties from molecular to device level 197. 198 Oligomer 155 exhibited an absorption maximum at 424 nm, which was assigned to the transition from individual dendrons because of the meta ‐linkage. In contrast, owing to the insertion of electron‐poor cyano groups (→ 156 ), an additional charge transfer band appeared at 511 nm.…”
Section: Bulk‐heterojunction Solar Cells Based On Star‐shaped Dyesmentioning
confidence: 99%
“…Dendrimer 5d showed a broad absorption in the range 300-700 nm and a reduced bandgap of 1.7 eV, giving an efficiency of 1.3 %. Kopidakis and coworkers have developed such an oligothiophene (5e) with electron-deficient tricyanobenzene as core and electron-rich dendrons [62]. Compared to the control dendrimer with the same structure but without the electron-deficient core (5e-1), the appending electrondeficient core in 5e-2 planarizes the structure and lowers the bandgap, thus leading to enhanced structure order in bulk heterojunction films.…”
Section: Oligothiophenesmentioning
confidence: 99%
“…Notably, despite its lower bandgap, an expected larger J SC for 5e-2 as comparison to 5e-1 was not recorded. The electron trapping effect in the cyanobenzene core can account for its lower J SC , impeding electron transfer to the acceptor [62]. Another approach for broadening the absorption is introducing acceptors into the terminal of oligothiophenes.…”
Section: Oligothiophenesmentioning
confidence: 99%